2017
DOI: 10.1371/journal.pone.0184015
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics, community of parasites, and resistance to rodenticides in an urban brown rat (Rattus norvegicus) population

Abstract: Brown rats are one of the most widespread urban species worldwide. Despite the nuisances they induce and their potential role as a zoonotic reservoir, knowledge on urban rat populations remains scarce. The main purpose of this study was to characterize an urban brown rat population from Chanteraines park (Hauts-de-Seine, France), with regards to haematology, population genetics, immunogenic diversity, resistance to anticoagulant rodenticides, and community of parasites. Haematological parameters were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 94 publications
1
47
0
Order By: Relevance
“…Surprisingly, the prevalence of Bartonella-DNA estimated by PCR was lower (31.4%; 27/86). The authors of this study were careful with identification of the Bartonella species detected in the rats, but short sequences of the obtained pap31 amplicons were identical to B. henselae sequences (Desvars-Larrive et al, 2017).…”
Section: Francementioning
confidence: 87%
See 1 more Smart Citation
“…Surprisingly, the prevalence of Bartonella-DNA estimated by PCR was lower (31.4%; 27/86). The authors of this study were careful with identification of the Bartonella species detected in the rats, but short sequences of the obtained pap31 amplicons were identical to B. henselae sequences (Desvars-Larrive et al, 2017).…”
Section: Francementioning
confidence: 87%
“…Indeed, R. rattus might not have become established in the West Nile until the 1950s or even the 1960s as this rat was first identified in 1958 in the Ituri District of the DR Congo, which lies across the border from the West Nile Region (Borchert et al, 2007). This is perhaps not surprising as Hopkins (1949) suggested that R. rattus was first introduced to Uganda in the early Twentieth Century, a date that agrees with Delany's belief that this rat species first appeared in the country around 1910 (Delany, 1975). In this part of Africa, outsiders were restricted and movement of crops was limited until 1914 when the region became a British protectorate (Borchert et al, 2007).…”
Section: Distribution Of Bartonella In Rat Populations Within Urban Tmentioning
confidence: 89%
“…These mutations can result in single nucleotide polymorphisms (i.e., SNPs) (Richardson et al, 2017;Combs et al, 2018a,b) or rearrangements resulting in different numbers of small repeating sequences (e.g., microsatellites) (Gardner-Santana et al, 2009;Kajdacsi et al, 2013). Using these tools, researchers can infer historical movements by identifying the distances between relatives (e.g., parents and offspring; Costa et al, 2016;Glass et al, 2016), and identifying potential migrants (e.g., individuals genetically assigned to a population other than the one in which they were caught; Kajdacsi et al, 2013;Berthier et al, 2016;Desvars-Larrive et al, 2017). These methods have the benefit of supporting large sample sizes (e.g., 1220 in Combs et al, 2018a), but they are limited to detecting first-generation migrants and movements during which rats mate and are reproductively successful, underestimating true levels of connectivity among populations (Richardson et al, 2017).…”
Section: Home Rangementioning
confidence: 99%
“…Mate-searching is also an important driver of dispersal, with rats (particularly males) extending their movements in search of mates (Davis et al, 1948;King, 1950;Glass et al, 2016). Sex-biased dispersal has been documented in Norway rats where the majority of migrants are often reproductively mature males (Gardner-Santana et al, 2009;Kajdacsi et al, 2013;Desvars-Larrive et al, 2017). Sex-biased dispersal has been further evidenced by close proximity among related females caught at a fine spatial scale, suggesting that females moved shorter distances than males in the same population (Desvars-Larrive et al, 2017).…”
Section: Dispersalmentioning
confidence: 99%
See 1 more Smart Citation